2010
DOI: 10.1016/j.tripleo.2009.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of mandibular advancement devices in positional and nonpositional OSA patients

Abstract: Objective The aim of the study was to investigate treatment outcome of mandibular advancement devices (MADs) for positional and non-positional obstructive sleep apnea (OSA). Study design Forty-two positional (supine apnea-hypopnea index [AHI] ≥ 2x’s lateral AHI) and 30 non-positional (supine AHI < 2x’s lateral AHI) OSA patients performed two-nights of sleep study before and after insertion of MADs. Results The decreases in apnea severity based on a reduction in the overall and supine AHI values after MADs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
57
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
4
57
0
4
Order By: Relevance
“…13,[20][21][22][23] In addition, the majority of studies evaluating the effect of sleep position on OA m efficacy have reported that OA therapy is more efficacious in patients with sdO-SA. 13,16,17,[24][25][26] However, other studies did not find a difference in success rates between non-sdOSA and sdOSA patients.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…13,[20][21][22][23] In addition, the majority of studies evaluating the effect of sleep position on OA m efficacy have reported that OA therapy is more efficacious in patients with sdO-SA. 13,16,17,[24][25][26] However, other studies did not find a difference in success rates between non-sdOSA and sdOSA patients.…”
mentioning
confidence: 85%
“…9 The most frequently and widely used defi nition is a supine AHI ≥ twice as high as the non-supine AHI and was fi rst described by Cartwright et al 5 The prevalence of sdOSA in a general population ranges the literature from 46% to 80%, which was comparable to the prevalence of sdOSA in the general population. 13,16,17 These results, however, do not reveal the evolution of sdOSA once OA m has started, and the prevalence of sdOSA under OA m therapy is still unknown. Interestingly, in some patients sdOSA and non-sdOSA are dynamic phenotypes 8 : weight reduction may convert a non-sdOSA patient into sdOSA.…”
mentioning
confidence: 92%
“…However, practice trends elsewhere show that duoblocs are increasingly being used. Given conflicting results between earlier studies with monoblocs [2][3][4][5] including present study by Takaesu et al 7 and recent study by Sutherland et al 11 that used a particular type of duobloc, large-scale randomized controlled trials that test different device designs on different populations with a uniform definition of P-OSA are warranted to provide more clarity. Until then, the association between MADs and P-OSA is more complex than meets the eye!…”
mentioning
confidence: 67%
“…1 However, prediction of treatment outcome with MADs remains a key unresolved issue, this perhaps becoming more complicated as a plethora of devices have evolved that differ in their design, fabrication, adjustability, allowance of either vertical or lateral jaw movement, and plate connectors. Based on data from earlier studies, [2][3][4][5] factors that predict successful MAD treatment include younger age, lower body mass index (BMI), smaller neck circumference, and supinedependent or positional OSA (P-OSA). 6 However, none of the prior studies 2-5 compared the efficacy of MADs with continuous positive airway pressure (CPAP).…”
mentioning
confidence: 99%
See 1 more Smart Citation